MENGGALI DIMENSI EMOSIONAL DALAM ANTOLOGI IMPROMPTU TERZINA: TINJAUAN PSIKOLOGI SASTRA TERHADAP KARYA EWITH BAHAR - Rahmadhani, Nabila; Aina, Nur; Zamriati, Neldia; Novia Putri, Inke; Elmustian (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to reveal the psychological dynamics of the poet in Impromptu Terzina by Ewith Bahar through Freud’s psychoanalytic approach. The research focuses on how the terzina structure functions as a medium of sublimation for the poet’s inner expressions. The analysis was conducted descriptively and analytically by examining diction, symbols, and poetic structure representing Freud’s three aspects of personality: the id, ego, and superego. The findings show that the id appears through spontaneous emotional impulses, the ego organizes reflective awareness toward reality, and the superego embodies moral values and inner peace. The terzina structure serves not only as an aesthetic form but also reflects the poet’s psychological order in channeling inner conflict into emotional harmony. Thus, Impromptu Terzina demonstrates that poetry can act as a means of sublimation and self-healing while offering a new perspective in psychoanalytic literary studies that link Freud’s theory with poetic form and structure.